ANALISA PENGARUH CORPORATE IMAGE DAN CUSTOMER SATISFACTION TERHADAP STORE FIRM PERFORMANCE PADA INDUSTRI RITEL KHUSUSNYA CONVENIENCE STORE DI SURABAYA - Djuali, Stephanie Cynthia (Business Accounting Review, 2015)
This study aimed to examine the influence of corporate image on store firm performance through customerâs satisfaction as intervening variables in the retail company in Surabaya. The sample in this study was 35 retail companies in Surabaya. Data obtained by spreading the questionnaire to the companies. This study used path analysis techniques with PLS (Partial Least Square). From the test conducted were found significant positive influence of corporate image on customerâs satisfaction, and also positive and significant influence on the corporate image to the store firm performance. In this study, the customerâs satisfaction had a significantly negative affect on store firm performance at retail convenience store company in Surabaya.